Application of Maggot Cultivation Technology to Strengthen Competitiveness of Sustainable Food Micro, Small, and Medium Enterprises - Kastaman, Roni; Syahmurman, Faizal; Rahmah, Devi M.; Ardiansah, Irfan; Kurniawan, Koko Iwan Agus; Januardi, Januardi; Puspita, Puspita; Nurliasari, Dessy; Hanifah, Aisyah (The Journal of Experimental Life Science, 2026)
The cultivation of maggots through the larvae of black soldier fly (Hemetia illucens) is increasingly recognized as a viable solution for organic waste management and alternative protein production. However, its integration into village-based enterprises and implications for Micro, Small and Medium Enterprises (MSMEs) competitiveness remain underexplored. This study examines how maggot cultivation strengthens food MSMEs using a circular economy framework and SWOT (strengths, weaknesses, opportunities, and threats) analysis. The study was conducted at Village-Owned Enterprises (Badan Usaha Milik Desa and abbreviated by BUMDes in Bahasa Indonesia) Kerta Setra Utama in Tasikmalaya, Indonesia. A mixed-methods approach was applied, combining qualitative observation with quantitative analyses of waste reduction, maggot yield, and protein content. Results showed a 65% reduction in organic waste within 5 days, a 28% increase in maggot biomass across 6 production cycles, and a 30% increase in household incomes. Using poultry manure as a substrate reduced waste by 31.2%. Furthermore, the substrate resulted in 114 g of dry weight.kg-1 of feed as well as 25.26% crude protein in less than eight days. SWOT analysis identified key constraints in community participation, institutional support, and technological capacity. There were opportunities that came from the integration of the circular economy and the expansion of green markets. The findings demonstrate that rural enterprises can effectively transform organic waste into economic value through maggot farming. Policy recommendations emphasize capacity building, green financing, and digital market integration to enhance scalability and long-term impact.